Analisis Produktivitas Tenaga Kerja Pada Pekerjaan Pile Cap Menggunakan Macro VBA - Kombong, Eka Priska (Universitas Ibn Khaldun, 2025)
Increased development is directly proportional to the absorption of labour in the construction sector. Nevertheless, the large number of workers does not guarantee the quality and productivity of a job. Labor productivity is the first indicator to assess the success of construction work so it needs to be analysed. This study aims to calculate the productivity of labours on pile cap for the construction of the Manohara Hotel, Yogyakarta, using Monte Carlo simulations and the Macro VBA program. The results of the analysis are divided into three parts, among others: the work productivity of the work floor, the installation of bricks as pile cap walls and the work of pile cap reinforcement. In general, the results of the study show that the productivity of the pile cap work is quite good, where the productivity of the work floor is 0.22 m3/hour with an average idle time of 12 minutes or an average worker break of 13.04% during the working time from 18.30–20.00 WIB; the lowest brick installation productivity was 12.38 bricks/hour with an idle average of 8.3 minutes or 14.27% during processing time from 15.30-16.30 WIB; and the lowest reinforcement installation productivity is in the bottom reinforcement work of 60 reinforcement/hour with an average idle of 10.69 minutes or an ineffective worker time of 50.8% of the total work time.